Spectrophotometric method for evaluating proteolysis in cheeses and aromatic additives with a cheesy taste - D. S. Myagkonosov; D. V. Abramov; E. G. Ovchinnikova; V. N. Krayushkina (Пищевые системы, 2021)
The spectrophotometric method for measuring protein content can be used to evaluate the degree of proteolysis in cheeses. At a wavelength of 280 nm, tryptophan and tyrosine are absorbed, a high amount of them is found in casein, the main protein of cheese mass. It was found that the value of the absorbance coefficient of the solution of proteins extracted from flavoring additives with cheese flavor (FA) and cheeses depends on the degree of proteolysis of proteins in the cheese mass and differs in FA and different types of cheeses. The highest absorbance coefficient is observed in the FA samples A1%1cm = 10.30, in which from 65 to 81% of the protein is converted into a soluble state. In cheeses, the degree of proteolysis is from 23 to 33%, and the absorbance coefficient of solution is from 1.1 to 2.4 (with the exception of Cheddar cheese), which indicates an incomplete transition of amino acids absorbing radiation at 280 nm into the extract released from cheeses. Using the spectrophotometric method, the results of measuring the content of soluble protein in cheeses and FA, strictly correlating with the results achieved by the Kjeldahl method (R2 > 0.81), can be obtained. To get reliable results of evaluating the content of water-soluble protein in cheeses, it is necessary to carry out measurements on a sample of cheeses belonging to the same species group, having the same specificity of proteolysis and slightly different absorbance coefficient between samples within the instance.